GIScience and cancer: State of the art and trends for cancer surveillance and epidemiology. Issue 15 (30th May 2019) - Sahar, Liora; Foster, Stephanie L.; Sherman, Recinda L.; Henry, Kevin A.; Goldberg, Daniel W.; Stinchcomb, David G.; Bauer, Joseph E.
Abstract : Maps are well recognized as an effective means of presenting and communicating health data, such as cancer incidence and mortality rates. These data can be linked to geographic features like counties or census tracts and their associated attributes for mapping and analysis. Such visualization and analysis provide insights regarding the geographic distribution of cancer and can be important for advancing effective cancer prevention and control programs. Applying a spatial approach allows users to identify location‐based patterns and trends related to risk factors, health outcomes, and population health. Geographic information science (GIScience) is the discipline that applies Geographic Information Systems (GIS) and other spatial concepts and methods in research. This review explores the current state and evolution of GIScience in cancer research by addressing fundamental topics and issues regarding spatial data and analysis that need to be considered. GIScience, along with its health‐specific application in the spatial epidemiology of cancer, incorporates multiple geographic perspectives pertaining to the individual, the health care infrastructure, and the environment. Challenges addressing these perspectives and the synergies among them can be explored through GIScience methods and associated technologies as integral parts of epidemiologic research, analysis efforts, and solutions. The authors suggest GIScience is a powerful tool for cancer research, bringing additional context to cancer data analysis and potentially informing decision‐making and policy, ultimately aimed at reducing the burden of cancer. Abstract : The current state and evolution of geographic information science (GIScience) in cancer research is explored by addressing fundamental topics and issues regarding spatial data and analysis that need to be considered. GIScience is a powerful tool for cancer research, bringing additional context to cancer data analysis, potentially informing decision making and policy, and ultimately reducing the burden of cancer.